Biomimicry emulating the water system of Waling-waling for sustainable architecture - Estilloso, Eiries Von B.; Songcayauon, Ryan C. (2017)
The setting of the study, Philippines, suggests problems on high relative humidity that causes thermal discomfort. The thesis aimed to use biomimicry in finding solutions to this problem to be emulated into building design and technology that will make use of the problem as an advantage to make the building sustainable. For this, it explored and studied the water system of the Waling-waling (Vanda/Euanthe Sanderania). Studying the water system includes gathering of related literature concerning its physiology. Through design-by-analogy, the water system was then broken down into main parts and processes essential for the system specifically: roots for absorption and condensation of water vapor, stem for the distribution, and leaves for its release. These analogies were then emulated in a simulation through an actual model. The analogies were then emulated in a simulation through an actual model. The model was a representation of a room and its surroundings that exhibit the water system of the organism. There are three main parts of the simulation model, representing the main parts of the water system. First, the exhaust fan that represents the roots, which exhibited absorption. Next, is a metal coil buried 1.5m underground connected to a series of PVC pipes which represents part of the roots and the stem, that exhibited the condensation. Lastly, the water tank that represents the storing capacity of the organism. The results of the simulation were obtained through observations and calculations. The results suggest that the water that can be condensed and gathered is a) directly proportional to absolute humidity; b) indirectly proportional to the precipitation in the surroundings; c) indirectly proportional to the time of the day, where the time of day increases the water gathered decreases. The results also show that at zero precipitation, the average water gathered per hour is 61.11ml, with 0.23ml of water per air change; 26.92ml of average water gathered per hour with 0.10ml of water per air change during drizzle or less precipitation; and lastly, during rainy condition, the average water gathered per hour is 16.67ml with 0.06ml per air change. These simulation results were then emulated for architectural translation. For further study on these mechanisms, a comparative study by manufacturing simulation models with varying factors can be done. Studying the potability of the water obtained from the condensation will further emphasize possible solutions in designing a sustainable architecture.
Thesis (BS Architecture) -- University of the Philippines Mindanao, June 2017